On the turning modeling and simulation: 2D and 3D FEM approaches. (8th August 2014) - Asad, M.; Mabrouki, T.; Ijaz, H.; Aurangzeb Khan, M.; Saleem, W.
<x content-type="archive" xml:space="preserve">Abstract</x> For qualitative prediction of chip morphology and quantitative prediction of burr size, 2D and 3D finite element (FE) based turning models have been developed in this paper. Coupled temperature-displacement machining simulations exploiting the capabilities of Abaqus® with a particular industrial turning insert and a newly proposed geometrical version of this insert have been performed. Limitations of 2D models in defining the chip morphologies and surface topologies have been discussed. The phenomenological findings on the Poisson burr (Side burr) formation using 3D cutting models have been highlighted. Bespoke geometry of the turning insert has been found helpful in reducing the Poisson burr formation, as it reduces the contact pressures at the edges of tool rake face-workpiece interface. Lower contact pressures serve to decrease the material flow towards workpiece edges (out of plane deformation). In contrast, higher contact pressures at tool rake face-workpiece interface lead to more material flow towards workpiece edges resulting in longer burr. Simulation results of chip morphologies and cutting forces for turning an aluminum alloy A2024-T351 have been compared with the experimental ones. Finally, it has been concluded that the newly proposed geometry of the insert not only decreases the burr but also helpful in lessening the magnitude of tool-workpiece initial impact.